Leading and Managing Geographically Isolated Schools in a VUCA Environment: A Transcendental Phenomenological Study of Principals in Romblon, Philippines - Vanly F. Alvaran; Philip R. Baldera; Aljay Marc C. Patiam; Mhilwin A. Esto; Rothy Star Moon S. Casimero; Rosanna Z. Fortaleza; Carlito E. Añonuevo; Susie F. Fallaria; Mary Grace M. Falcunitin; Maricar L. Ramirez; Ailyn F. Tablada; Pinky Rose D. Dalisay; Elmer C. Gacilo; Fe Asuncion Madeja; Ailyn F. Arcasitas (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
School principals in geographically isolated and disadvantaged areas operate under volatile, uncertain, complex, and ambiguous conditions that intensify the demands of educational leadership and management. This study explored how principals in geographically isolated schools in Romblon, Philippines experienced and integrated authentic leadership and educational management within a VUCA environment. Method: Using transcendental phenomenology, the study engaged nine elementary and secondary school principals selected through purposive sampling. Data were generated through semi-structured interviews and supplementary document review. Analysis followed epoché, phenomenological reduction, horizontalization, clustering of meaning units, and synthesis of textural and structural descriptions. Results: Findings showed that authentic leadership was enacted through vision anchored on learner needs, collaborative influence, Filipino cultural values, presence, trust, and service. Educational management was performed through structured monitoring, role clarification, strategic resource prioritization, policy alignment, delegation, and operational discipline. VUCA conditions were experienced through weather disruptions, transportation barriers, unclear policies, resource scarcity, staffing limitations, and changing learning modalities. Elementary school contexts required more direct, hands-on, and overlapping leadership roles, whereas secondary contexts involved broader curriculum, governance, and coordination demands. Conclusion: The transcending essence of the phenomenon was values-driven resilience through integrated authentic leadership and educational management. To lead and manage a geographically isolated school authentically meant serving with heart, deciding with integrity, organizing with discipline, adapting with resilience, and sustaining education through collective school-community strength.